2018
DOI: 10.1002/ijc.31647
|View full text |Cite
|
Sign up to set email alerts
|

Circulating enterolactone concentrations and prognosis of postmenopausal breast cancer: assessment of mediation by inflammatory markers

Abstract: Higher lignan exposure has been associated with lower all-cause mortality (ACM) and breast cancer-specific mortality (BCSM) for postmenopausal breast cancer patients. However, the biological mechanisms underpinning these associations are still unclear. We investigated for the first time whether and to what extent the association between enterolactone (ENL), the major lignan metabolite, and postmenopausal breast cancer prognosis is mediated by inflammatory biomarkers. Circulating concentrations of ENL and infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
(92 reference statements)
0
18
0
Order By: Relevance
“…Therefore, non-detectable values for IL-6 were set to missing, while non-detectable values for the remaining inflammatory markers were set to half the detection limit due to highly skewed distributions [ 24 ]. Missing values above fit curve range as well as extreme outliers were set to missing, resulting in available biomarker concentrations for between 2729 (e.g., IL-6) and 2761 patients (e.g., TNF-α) [ 25 ] ( Supplementary Tables 1A and 1B ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, non-detectable values for IL-6 were set to missing, while non-detectable values for the remaining inflammatory markers were set to half the detection limit due to highly skewed distributions [ 24 ]. Missing values above fit curve range as well as extreme outliers were set to missing, resulting in available biomarker concentrations for between 2729 (e.g., IL-6) and 2761 patients (e.g., TNF-α) [ 25 ] ( Supplementary Tables 1A and 1B ).…”
Section: Methodsmentioning
confidence: 99%
“…Interviews were conducted by trained interviewers using standard questionnaires person to person at recruitment and by telephone in 2009 at follow-up for postdiagnosis physical activity and other lifestyle, personal, and clinical characteristics. Information on vital status was collected from population registries in 2009 [10] and 2015.…”
Section: Methodsmentioning
confidence: 99%
“…Recent research suggests that much of the effect of lignans may be as a result of antiinflammatory influences, which we have not as yet adequately explored in our clinical trial specimens [55][56][57]. Indeed, our companion study in an immunocompetent mouse model of triple negative breast cancer suggested that SDG, in doses producing equivalent enterolactone and enterodiol blood levels as in our human pilot study, suppressed NFκB activation [14].…”
Section: Discussionmentioning
confidence: 79%